Effect of the phase composition and crystallite size of sol-gel TiO2 nanoparticles on the acetaldehyde photodecomposition (Superficies y Vacío, 2012)
TiO2 nanoparticles with attractive physicochemical properties have synthesized by means of the sol-gel method and acid hydrolysis. The obtained nanoparticles have characterized by the XRD-Rietveld refinement, BET and TEM techniques, and tested in the photodecomposition of acetaldehyde. The degree of decomposition of acetaldehyde by the sol-gel TiO2 nanoparticles was directly proportional to the brookite mass fraction but inversely proportional to the anatase mass fraction and crystallite size.